Relationship between Company Characteristics and Divided Policy: Examining the Impact of Company Characteristics on Dividend Policy (Journal of Advances and Scholarly Researches in Allied Education, 2019)
It means that the managements desire stable divided policy. The regression coefficients of operating profit have positive values in most of the cases and found statistically significant for eight years out of sixteen years of the study. This indicates that there was a positive relationship between profit after tax and dividend paid, which support the hypothesis. The regression coefficients of interest paid have negative values in most of the years and were also found statistically significant for six years out of sixteen years of the study.